Selective language deterioration in chronic schizophrenia. Issue 6 (June 1981) - Silverberg-Shalev, R; Gordon, H W; Bentin, S; Aranson, A
Abstract : Chronic schizophrenics as a group were inferior to controls on tests of neuropsychological function. When divided into groups according to length of illness they differed from each other primarily in tests of language. No other deficits in cognitive function progressed; the performance of the patients on memory, visuo-spatial tasks, rate of information processing and abstract thinking did not decline according to length of illness. The results indicate that chronic schizophrenia is characterised by a selective deterioration of language, which correlates with the notion that schizophrenia may be associated with left hemisphere dysfunction.